2019
DOI: 10.3389/fphys.2019.00768
|View full text |Cite
|
Sign up to set email alerts
|

Foam Rolling as a Recovery Tool Following Eccentric Exercise: Potential Mechanisms Underpinning Changes in Jump Performance

Abstract: Purpose Recovery from exercise-induced muscle damage (EIMD) is paramount in sports performance. Foam rolling (FR) has been suggested to improve acute performance; however, the ability to facilitate recovery from eccentric (ECC) exercise remains unclear. Methods Eleven males undertook 6 × 25 ECC knee extensions to induce muscular damage. Immediately, 24, 48, and 72 h post-training countermovement jump (CMJ), maximal voluntary isometric contraction (MVIC), pressure-pain t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
(74 reference statements)
0
14
1
1
Order By: Relevance
“…The algometer is also used to measure the PPT reliably, both at the muscular and joint levels, after FR routine. It is also used after exercise induced muscle damage and FR recovery ( Pearcey et al, 2015 ; Correira, 2016 ; Casanova et al, 2017 ; Drinkwater et al, 2019 ; Table 5 ). Likewise, just like MM, functional tests, such as the sit-and-reach or weight-bearing lunge tests, are usual tools to assess the effectiveness of FR on ROM ( Sullivan et al, 2013 ; Halperin et al, 2014 ; Grieve et al, 2015 ; Peacock et al, 2015 ; Škarabot et al, 2015 ; Kelly and Beardsley, 2016 ; Patel et al, 2016 ; Boguszewski et al, 2017 ; Grabow et al, 2017 ; Jung et al, 2017 ; Paz et al, 2017 ; Sağiroğlu, 2017 ; Garcia-Gutiérrez et al, 2018 ; Phillips et al, 2018 ; Guillot et al, 2019 ; Pathania and Muragod, 2019 ; Somers et al, 2019 ; Williams and Selkow, 2019 ; Table 6 ).…”
Section: Foam Rollingmentioning
confidence: 99%
“…The algometer is also used to measure the PPT reliably, both at the muscular and joint levels, after FR routine. It is also used after exercise induced muscle damage and FR recovery ( Pearcey et al, 2015 ; Correira, 2016 ; Casanova et al, 2017 ; Drinkwater et al, 2019 ; Table 5 ). Likewise, just like MM, functional tests, such as the sit-and-reach or weight-bearing lunge tests, are usual tools to assess the effectiveness of FR on ROM ( Sullivan et al, 2013 ; Halperin et al, 2014 ; Grieve et al, 2015 ; Peacock et al, 2015 ; Škarabot et al, 2015 ; Kelly and Beardsley, 2016 ; Patel et al, 2016 ; Boguszewski et al, 2017 ; Grabow et al, 2017 ; Jung et al, 2017 ; Paz et al, 2017 ; Sağiroğlu, 2017 ; Garcia-Gutiérrez et al, 2018 ; Phillips et al, 2018 ; Guillot et al, 2019 ; Pathania and Muragod, 2019 ; Somers et al, 2019 ; Williams and Selkow, 2019 ; Table 6 ).…”
Section: Foam Rollingmentioning
confidence: 99%
“…Although Behm and Wilke pointed out that the evidence supporting the fact that the primary mechanisms underlying foam rolling are the release of myofascial restrictions is insufficient [ 20 ], foam rolling intervention could be useful in sports and rehabilitation settings, because of its increment effect on ROM and pain threshold. Regarding the recovery effects after foam rolling, previous studies have shown that foam rolling intervention aids in the recovery from muscle damage immediately after 24, 48, and 72 h after ECC exercise [ 21 , 22 ]. Moreover, Romero-Moraleda and colleagues investigated the effect of 300-s foam rolling on the damaged muscle two days after exercise, in which the symptoms of DOMS and muscle function loss peaked, and showed significant improvement in DOMS and function loss [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beier et al [52] observed that FR does not produce measurable benefits in terms of the sensation of fatigue after 24 hours. On the other hand, Drinkwater et al [53] emphasized that foam rolling appears to improve performance in the later stages of recovery following eccentric exercise, which might explain the positive effects observed after 96 hours. Foam rolling was also beneficial for minimizing muscle soreness in research by McDonald et al [54].…”
Section: Domsmentioning
confidence: 99%